2021
DOI: 10.1155/2021/5576959
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections and Perioperative Optimization of Host Immunity by Selection of Anesthetics

Abstract: Surgical site infections are significant health care issues, and efforts to mitigate their occurrence have been ongoing worldwide, mainly focusing to reduce the spillage of microbes to the otherwise sterile tissues. Optimization of host immunity has been also recognized including temperature regulation (normothermia), adequate oxygenation, and glucose management. A number of papers have described the role of anesthetics in host immunity. The role of anesthetics in postoperative outcomes including surgical site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 100 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…However, despite these multifaceted benefits, postoperative infections after laparoscopic radical nephrectomy can impair the recovery process and increase hospitalization costs. Although the associated risks are relatively low, infection remains a concern, emphasizing the necessity of strict surgical protocols and meticulous postoperative management 17,18 . This type of infection may exist in various forms, from local wound infections to urinary tract infections and even systemic sepsis; this depends on the characteristics and scope of bacterial infiltration 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite these multifaceted benefits, postoperative infections after laparoscopic radical nephrectomy can impair the recovery process and increase hospitalization costs. Although the associated risks are relatively low, infection remains a concern, emphasizing the necessity of strict surgical protocols and meticulous postoperative management 17,18 . This type of infection may exist in various forms, from local wound infections to urinary tract infections and even systemic sepsis; this depends on the characteristics and scope of bacterial infiltration 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the associated risks are relatively low, infection remains a concern, emphasizing the necessity of strict surgical protocols and meticulous postoperative management. 17,18 This type of infection may exist in various recuperation time and inflate cumulative medical expenses. In addition, relevant studies have shown that infection is a prevalent complication during the treatment of patients with this disease, and complications have a significant impact on their postoperative survival.…”
Section: Discussionmentioning
confidence: 99%
“…20 Given the intricacies and specialized nature of the procedure, understanding the risk factors specific to SSIs in laparoscopic radical nephrectomy for RCC becomes paramount. 21 This study's focus on laparoscopic radical nephrectomy for RCC is essential as it addresses a significant gap in the literature, where generalized findings from broader urological surgeries might not fully apply. The predictive value of NLR and PLR, combined with an in-depth understanding of operating room factors, can provide invaluable insights into the risk of SSIs following this specific surgery.…”
Section: Introductionmentioning
confidence: 99%
“…While laparoscopic techniques offer many advantages over traditional open surgeries, they come with unique challenges and risks, especially concerning SSIs 20 . Given the intricacies and specialized nature of the procedure, understanding the risk factors specific to SSIs in laparoscopic radical nephrectomy for RCC becomes paramount 21 . This study's focus on laparoscopic radical nephrectomy for RCC is essential as it addresses a significant gap in the literature, where generalized findings from broader urological surgeries might not fully apply.…”
Section: Introductionmentioning
confidence: 99%
“…As a beneficial supplement to centralized power generation, distributed power generation can enhance power supply stability. Distributed power generation has unparalleled advantages in energy substitution, environmental protection, improving system power supply reliability and reducing power supply costs [1][2].…”
Section: Introductionmentioning
confidence: 99%